Pengaruh Budaya Akseptor KB terhadap Penggunaan KB IUD di Wilayah Kerja Puskesmas Paringin Tahun 2022 - Mahmudah Mahmudah; Istiqamah Istiqamah; Noval Noval; Ika Friscila (Jurnal Rumpun Ilmu Kesehatan, 2023)
. IUDs are one of the most effective and safe long-acting contraceptives, but the use of this method of contraception is still very low. The purpose of the study was to determine the influence of birth control acceptor culture on the use of IU birth control. The research method is a quantitative analytical survey with a cross sectional approach. The population is all family planning acceptors who visited the Paringin City Health Center, Balangan Regency, South Kalimantan from September to November 2022, totaling 111 people with an accidental sampling technique of 53 respondents. Chi square data analysis technique. The results showed that the majority used contraception as much as 32 (60.4%), good knowledge as much as 24 (45.3%), positive attitude as much as 26 (49.1%), positive confidence as much as 32 (60.4%), positive value as much as 35 (66%). There is an influence of attitude (pvalue 0.033), trust (pvalue 0.000) and value on IUD birth control use with value (pvalue 0.000). There was no effect of birth control acceptor knowledge on IUD KB Use (pvalue 0.379). The implication of the research results is that health workers through stakeholders can provide education or information about contraception.